Analisis Model Konsiderasi dan Klarifikasi Nilai dalam Upaya Meningkatkan Kemampuan Afektif Siswa pada Mata Pelajaran Fisika - Syifa Alfiah Fahrunnisa; Acep Kusdiwelirawan; Mirzanur Hidayat (Universitas Muhammadiyah Purworejo, 2020)
This study aims to determine the models and criteria for increasing affective femininity. This research was conducted at SMAN 1 Ciruas in the first semester of the 2018-2019 school year. This study emphasizes 34 models of consideration and value classification. This study uses a qualitative and quantitative approach with descriptive analysis methods. After the learning process model is considered and adjusted to the CIPP program (Context, Input, Process, Products) The results of the study show that: (1) There is an increase in effective ability in the learning model of consideration and classification of values ​​(2) there is a meeting of cognitive and psychomotor abilities. (3) Evaluation of the model of product variable consideration is 79,35 at 72,91≤ Score < 93,74 means that it includes the Effective category. (4) Product variables in the model average value of 82,14 in 72,91 ≤ Score < 93,74 is included in the effective category.